THE USE OF SMARTPHONES IN DEVIANT BEHAVIORAMONG ADOLESCENTS IN THE GENENG VILLAGE, BOJONEGORO DISTRICT - Rahmawati, Rahmawati; Mulyani, Sri; Firdaus, Wahyuning Jannatul (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACTCommunication tools that have more capabilities as mentioned above are popularly known as smartphones. But behind the sophistication of technology that carried the smartphone, there are things that are very detrimental to its users, especially in adolescents. Negative internet content that is on smartphones such as online games, online gambling, pornography, and so on can have a bad influence so as to lead teens to deviate behavior. The purpose of this study was to determine the relationship between the use of mobile phones (smartphones) with behavior deviations in adolescents.Correlational analytic research design, with cross sectional approach. Population of 112 adolescents, sample of 79 respondents, sampling by simple random sampling. The independent variable is the use of mobile phones (smartphones), and the independent variable is deviation of behavior in adolescents. The instrument used questionnaire sheets, processing with editing, coding, scoring, tabulating and analyzing data with Chi-Square test with alpha value (? = 0.05).The results of this study were obtained from 79 respondents who were studied. There were a majority of respondents using smartphones positively, as many as 73 respondents (92.4%), the majority of respondents had good behavior as many as 74 respondents (93.7%), and there was a relationship between smartphone use and behavioral deviations in adolescents. in Geneng Village, Margomulyo Subdistrict, Bojonegoro Regency in 2019, with a significant value of 0,000 <? (0.05) and with a strong closeness (Phi / Cramer's of 0.907).In adolescents who use smartphones positively, it will affect their behavior towards good deeds. And vice versa, in adolescents who use smartphones negatively, it will affect their behavior towards deviant actions that follow or imitate all forms of bad behavior that they see. Keywords: Smartphone, Behavior, adolescents.